(untitled) - Takizawa, Matsuyo (New York, 1927)
This book introduce about the economic organization og Japan preceding the penetration of money economy, the development of money economy, the effect to money upon the development of towns...
Keywords: Tiền tệ,Money; Nhật Bản,Japan